Current understanding of Age-related macular degeneration - Swathi Kanduri (International Journal of Retina, 2020)
Age-related macular degeneration (AMD) is the leading cause of irreversible blindness in the elderly population 50 years of age or older in the developed countries. This review discusses the traditional clinical and histopathological presentation of AMD, epidemiology and genetics component in relation to the current understanding of the vascular nature of the disease. Therapeutic approaches to treat the disease are also included in the review.